2005
DOI: 10.1038/sj.jp.7211325
|View full text |Cite
|
Sign up to set email alerts
|

Work of Breathing During Nasal Continuous Positive Airway Pressure in Preterm Infants: A Comparison of Bubble vs Variable-Flow Devices

Abstract: The more labored and asynchronous breathing seen with bubble NCPAP may lead to higher failure rates over the long term than with VF-NCPAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
2
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 17 publications
4
51
2
9
Order By: Relevance
“…Clinical studies demonstrate increased work of breathing with constant flow CPAP systems compared with CPAP systems with variable flow capabilities. 17 Increasing the constant flow through a system with increased resistance may further encumber breathing. It is important for the respiratory therapist to understand the type of bubble CPAP system that is used and the effect that leak has on delivered pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies demonstrate increased work of breathing with constant flow CPAP systems compared with CPAP systems with variable flow capabilities. 17 Increasing the constant flow through a system with increased resistance may further encumber breathing. It is important for the respiratory therapist to understand the type of bubble CPAP system that is used and the effect that leak has on delivered pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the results found in these studies apply to CPAP applied to premature infants through the nasal route rather than through an endotracheal tube is unknown. One previous study has shown that infant flow NCPAP (IF-NCPAP) improves work of breathing (WOB) and respiratory asynchrony in premature infants compared to both B-NCPAP and V-NCPAP, 11 whereas another recent study found lower extubation failure rates and shorter duration of CPAP support with B-NCPAP compared to infant flow NCPAP in low-birth-weight infants ventilated for less than 14 days. 12 There are no published studies comparing respiratory parameters between B-NCPAP and V-NCPAP in infants while ensuring equal pressure delivery at the nasal prongs.…”
Section: Introductionmentioning
confidence: 99%
“…With this device, gas flowing through nasal prongs is facilitated during exhalation via a fluidic-flip design. 4,5 IF-CPAP has been shown to decrease oxygen requirement, improve respiratory effort [6][7][8][9] and prevent extubation failure in preterm infants when compared to traditional nasal prong systems and bubble CPAP. 9,10 However, nasal prong CPAP devices have been shown to damage the nares of infants, causing discomfort and rarely, long-term disfigurement.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 IF-CPAP has been shown to decrease oxygen requirement, improve respiratory effort [6][7][8][9] and prevent extubation failure in preterm infants when compared to traditional nasal prong systems and bubble CPAP. 9,10 However, nasal prong CPAP devices have been shown to damage the nares of infants, causing discomfort and rarely, long-term disfigurement. 11,12 Simple nasal cannula has recently been shown to generate positive end-expiratory pressure (PEEP) in preterm infants if air or oxygen is delivered at a high flow rate (i.e.…”
Section: Introductionmentioning
confidence: 99%